Endotoxins and Non-Alcoholic Fatty Liver Disease - Kessoku, Takaomi; Kobayashi, Takashi; Imajo, Kento; Tanaka, Kosuke; Yamamoto, Atsushi; Takahashi, Kota; Kasai, Yuki; Ozaki, Anna; Iwaki, Michihiro; Nogami, Asako; Honda, Yasushi; Ogawa, Yuji; et al. (Frontiers in Endocrinology, 2021)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. It occurs with a prevalence of up to 25%, of which 10–20% cases progress to nonalcoholic steatohepatitis (NASH), cirrhosis, and liver cancer. The histopathology of NASH is characterized by neutrophilic infiltration, and endotoxins from gram-negative rods have been postulated as a contributing factor. Elevations in endotoxin levels in the blood can be classified as intestinal and hepatic factors. In recent years, leaky gut syndrome, which is characterized by impaired intestinal barrier function, has become a significant issue. A leaky gut may prompt intestinal bacteria dysbiosis and increase the amount of endotoxin that enters the liver from the portal vein. These contribute to persistent chronic inflammation and progressive liver damage. In addition, hepatic factors suggest that liver damage can be induced by low-dose endotoxins, which does not occur in healthy individuals. In particular, increased expression of CD14, an endotoxin co-receptor in the liver, may result in leptin-induced endotoxin hyper-responsiveness in obese individuals. Thus, elevated blood endotoxin levels contribute to the progression of NASH. The current therapeutic targets for NASH treat steatosis and liver inflammation and fibrosis. While many clinical trials are underway, no studies have been performed on therapeutic agents that target the intestinal barrier. Recently, a randomized placebo-controlled trial examined the role of the intestinal barrier in patients with NAFLD. To our knowledge, this study was the first of its kind and study suggested that the intestinal barrier may be a novel target in the future treatment of NAFLD.